P83 Respiratory morbidity and assessment of respiratory risk factors in school aged children with severe neurological impairment. (15th November 2017) - Thomson, L; Gardner, L; Sharp, K; Davies, P
Abstract : Introduction: Respiratory morbidity is well documented in children with neurological impairment. Early intervention programmes to identify children at high risk are not well established. We proactively reviewed respiratory status of children with severe neurological impairment in local special schools to identify and manage those at high risk. Methods: School nurses identified all children with severe neurological impairment (GMFCS IV and V). All had a multidisciplinary respiratory assessment at school. Data was collected on respiratory health and risk factors. Appropriate investigations and respiratory plans were initiated. Results: 72/87 children identified by school nurses were assessed. 49 M:23 F. 47 (65%) had cerebral palsy. 9 (13%) patients had respiratory admissions to hospital in the previous year, 3 (4%) to PICU. 44 (61%) had <2 courses of antibiotics for respiratory infections in the last year, 15 (20%) 2–3 courses and 13 (18%)≥4 courses. 2 children were on home oxygen, 1 on NIV and 1 had a tracheostomy. 7 (10%) had established respiratory follow up. 21 (29%) patients had concerns about safety of swallow and 14 of these were orally fed. 14 (19%) had persistent symptoms of GORD. 27 (38%) had clinical signs or history of upper airway obstruction and 6 (8%) had abnormal oximetry. 27(%) had scoliosis which was severe in 4 (6%). All 9 patients with previous admissions had risk factors. 8 of 9 had multiple risk factors. 7 had swallowing concerns, 8 UAO and 1 GORD. All had≥=2 courses antibiotics in the previous year. No children with <2 courses of antibiotics were admitted. Only 4/17 children with significant respiratory morbidity (admission and/or ≥4 courses antibiotics) had a prior respiratory review. Conclusions: Although many children with severe neurological impairment did not have frequent respiratory infections or admissions, those with significant respiratory morbidity were predictable. They had multiple courses of antibiotics, admissions to hospital and significant risk factors. Many children had underlying risk factors which had not been addressed. We propose that a simple screening tool to identify children at risk and review risk factors for respiratory morbidity has the potential to improve the quality of life for this vulnerable group.